Reflective knowledge and potential architecture - CHUPIN, Jean-Pierre; BILODEAU, Denis; ADAMCZYK, Georges (ARCC Conference Repository, 2019)
This paper outlines an epistemological approach to "architectural project” with respect to the notion of potential architecture. We know, for example, that Rem Koolhaas and OMA's project for the Parc de la Villette probably had as much impact on architectural education and knowledge transfers, as Bernard Tschumi's prize-winning and built project. To explain this phenomenon in relation to the potential, and literally speaking, "virtual" nature of edification processes, we elaborate an analogy between the potential architecture of projects conceived in educational contexts, and the potential architecture of professional competition projects. A competition project clearly belongs to these activities of architectural thinking located exactly at the crossroads of discipline and profession. But there is another form of potential architecture that shares the same intermediate status, the same "in-between”. These are projects conceived in educational situations by architecture students. Yet, the understanding of these projects suffers some very recurrent contradictions in most European and North American schools. Indeed, depending on studios and professors, students are often brought to consider their projects as results (as objects), or as representations of a result (as images), and rarely as process of thought (as intellectual journeys). Architecture students often have many difficulties understanding why their projects are, for some, just weak simulations of professional activities, while for other academic disciplines, hardly more than forms of creative activities without real epistemological status: In other words, without real value in the production of knowledge. In most so-called "research universities”, Architecture is far from shining as a valid discipline of "thinking”. It is as if student's thesis neither had a real professional, nor a real disciplinary value: a bad study sketch as it were! Building on some of D.A. Schön's most durable hypotheses, particularly those stating that architectural knowledge lies at the core of reflective transfers between action and cognition, we investigate a model consisting in three fundamental aims of edification : construction, instruction and translation. These three aims are understood as complementary reflective sources of architectural knowledge that can be analyzed, in particular, on various corpuses of architectural competition projects whether or not these projects were prize winners or constructed. Schools of architecture share the burden of responsibility in a phenomenon of growing indifference towards disciplinary research specifically devoted to the architectural project, to the advantage of an over-investment towards technological instrumentation. Students, far from the (sometimes hasty) socio-political commitments of their elders, feel at present a certain anxiety concerning, not the future of Architecture itself, but the acquisition of peripheral knowledge and know-how in order to participate, as responsible individuals, in the blooming of society. For most of them, it is unclear whether the architectural project can be a vehicle of social changes and cultural mutations, given the contradictory messages (from professional as well as from academic circles) they are fed regarding both the pragmatic and epistemological value of their own projects.